Safety management in construction sites: Improper safety practices and employee turnover intention - Maisyarah, Mohamad Nor; Ting, Irene Wei Kiong; Leong, Mee Yeng; Azim Azuan, Osman; Asif, Jawad (Penerbit Universiti Malaysia Pahang, 2025)
There has been a significant increase in the number of recorded casualties within the construction business between 2020 and 2022, with a monthly rise in the frequency of such incidents. This study examines the correlation between safety practices and turnover intentions in the construction industry, focusing on registered construction companies in Kuala Lumpur. The target participants were Grade G5 to G7 construction companies registered with the Construction Industry Development Board (CIDB) in Wilayah Persekutuan Kuala Lumpur. The data was gathered through an online survey with 136 respondents and analysed using Structural Equation Modelling. A strong correlation was found between improper safety practices and turnover intention among construction workers. The findings hope to provide valuable insights for the construction industry to comprehend the impact of several variables on turnover intention. It also serves as an indicator for the most effective interpretation of employee turnover measurements to improve successful safety policies